Phytochemicals; Targeted-Based Therapeutic Approaches for Pigmentation Disorders - Ullah, Sana; Rabbia Shoaib; Siyar Khan; Aalia Masood (Open Access Indonesian Journal of Medical Reviews, 2023)
Skin pigmentation disorders refer to conditions that affect the color of the skin due to alterations in the production or distribution of melanin, the pigment responsible for skin color. The development of skin pigmentation is a complex process involving various signaling pathways, including the melanin synthesis pathway, the cyclic AMP pathway, and the Wnt signaling pathway. Dysregulation of these pathways can lead to the development of skin pigmentation disorders. Phytotherapeutic approaches have been increasingly studied as a potential treatment for skin pigmentation disorders. This literature review aimed to describe the basic mechanism of melanogenesis, various pathways involved in melanin formation, and certain diseases and their treatment through plant extracts. Plant extracts containing bioactive compounds such as flavonoids, phenolic acids, and tannins have been shown to have anti-pigmentary effects through various mechanisms, including inhibition of tyrosinase activity, reduction of melanin synthesis, and modulation of melanogenesis-related signaling pathways. Skin pigmentation disorders are complex and multifactorial conditions that can significantly impact a person's quality of life. Targeting the signaling pathways involved in pigmentation regulation, particularly through phytotherapeutic approaches, represents a promising avenue for the development of new therapies for these disorders.